PENERAPAN BELA DIRI MENCA SANGGE SEBAGAI PENDIDIKAN KARAKTER BUGIS MASYARAKAT LINGKUNGAN DARE’E, KABUPATEN BONE - Hezron Alhim Dos Santos; Rahyuddin Jide; Muhammad Zufikar; Dede Wahyudi; Maria Herlinda Dos Santos (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to determine the meaning contained in the Menca' Sangge movement and to find out the implications of Menca' Sangge in instilling Bugis character in society. This research was carried out empirically with the method used is an ethnographic method using a qualitative approach. The results of this study show the meaning contained in each movement of Menca' Sangge, namely the meaning implied in the movement of the stance, punch and parry. The implications of Menca' Sangge in instilling Bugis character in society are the contents of a sense of solidarity and kinship which are included in the teachings of Menca Sangge martial arts.